Motivation? Games! - Sánta Brigitta (2001)
In my thesis I would like to deal with motivation, I am going to give the definition of motivation and some theories that have developed since 1900.1 classified motivation, which is always depends on the teachers’ personality and the lessons’ aim. In my opinion games have an enormous influence on the learners, who can be motivated by games very well. I am going to give a definition of games, then I categorizy it according to their skills,language level and functions. I am going to write about hte usage and features of games, where and how games can be used. Our aim is to make learners participate in the learning process and give them "goals” unnoticed. My research is the third part which is based on my Questioneree.